A Road of her Own: Mobility in Sylvia Plath’s Poetry - Chouari, Anissa Abdelmaksoud (جامعة سوسة - كلية الآداب والعلوم الإنسانية, 2016)
This paper seeks to examine the idea of mobility in Plath’s poetry from a wide range of aspects. It proposes to analyze the female persona who, in her journey from “stasis” and darkness to movement and light, is best seen as a wanderer / flâneur who removes herself from the restriction of the urban and social world and withdraws further into the realm of nature. In her restlessness and within endlessly shifting borders between dream and reality, fixity and mobility, ascent and descent, the persona is engaged in a quest for self-identity. The journey becomes a Whitmanesque “Open Road”, and mobility is clearly displayed in the persona’s seemingly everlasting cyclic movement of death and rebirth as well as in her movement across gender borders. The paper also proposes to study the major technical devices that help convey the idea of mobility. Symbolism, mainly in Plath’s first and last volumes The Colossus and Ariel, foregrounds mobility in the way that Plath starts her poetic career with The Colossus, a stony figure, to end it with Ariel, an airy creature that is able to fly and ride the clouds. Metaphors are also suggestive of transformation and are emblematic of poetic growth.
Keywords: بلاث، سيلفيا، ت. 1963 م. -- الشعر الأمريكية -- الأدب الأمريكي -- النقد الأدبي